The Diversity of Liverworts in the Dolok Sordang Sub-District of Sipirok, South Tapanuli, Indonesia - Nurmaini Ginting; Melvariani Syari Batubara (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
Research conducted in the village of Dolok Sordang bordering the Natural Reserve of Dolok Sipirok. Found 21 types of liverworts which contains the thalloid liverworts and leafy liverworts. The family has one of the highest types of variation is Lejeuneaceae (6) followed by the Lepidoziaceae (4), Radulaceae (3), Lophocoliaceae (2), Marchantiaceae (2), Plaghiocilaceae (2), Metzegeriaceae (1) and the Aneuraceae (1). These types found on the substrate and elevation. Research data will be used as a reference to see the diversity of types of liverworts in the Natural Reserve of Dolok Sipirok